Preparing for and Recovering from Hurricane and Tropical Storm Damage to Tropical Fruit Groves in Florida - Jonathan H. Crane; Carlos F. Balerdi (EDIS)
The estimated destruction to tropical fruit crops caused by recent hurricanes and tropical storms (1992, 1994, 2004, 2005) was in the hundreds of millions of dollars. As with the aftermath of previous hurricanes, growers are currently assessing their options, such as replanting, rehabilitating damaged trees, and repairing equipment and irrigation systems. They are also assessing their economic situation.  This document is HS1022, one of a series of the Horticultural Sciences Department, UF/IFAS Extension. Original publication date September 2005.